2022
DOI: 10.1186/s43045-022-00263-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of ghrelin peptide among a sample of Egyptian patients with first episode of major depressive disorder

Abstract: Background Major depressive disorder (MDD) is a prominent psychiatric disorder that significantly reduces living quality and increases the risk of suicide. Ghrelin influences the central nervous system (CNS) and impacts reward, inspiration, and signaling pathways in addition to acting as an appetite signal. This case-controlled comparative study focused on the association between serum ghrelin levels and MDD. The study was done during September 2021 and March 2022 on 25 people with MDD and 25 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The published clinical data regarding the levels of ghrelin in individuals with depression remains controversial. While certain studies have indicated that there are no alterations in the levels of ghrelin among depressed patients, others have reported either decreased or increased levels [19,36]. Similar to our results, Barim et al reported that MDD patients had lower serum ghrelin than healthy controls suggesting that ghrelin may be involved in the pathophysiology of MDD [20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The published clinical data regarding the levels of ghrelin in individuals with depression remains controversial. While certain studies have indicated that there are no alterations in the levels of ghrelin among depressed patients, others have reported either decreased or increased levels [19,36]. Similar to our results, Barim et al reported that MDD patients had lower serum ghrelin than healthy controls suggesting that ghrelin may be involved in the pathophysiology of MDD [20].…”
Section: Discussionsupporting
confidence: 88%
“…The relationship between depression and ghrelin was also investigated in humans, and the results were inconsistent. Higher serum ghrelin concentrations were reported in MDD patients compared to healthy controls [11,18,19]. In contrast, other studies reported no differences or lower serum ghrelin concentration in patients with depression compared to controls [20,21].…”
Section: Introductionmentioning
confidence: 77%
“…There are several studies on the relationship between ghrelin concentration in blood and depression among adult, unmedicated participants. Some of the authors reported higher ghrelin levels in those diagnosed with depression ( 15 , 40 , 41 ), while others showed decreased ( 42 ) or similar ghrelin levels ( 43 45 ) in comparison to healthy participants.…”
Section: Relationship Between Ghrelin Concentration and Major Depress...mentioning
confidence: 99%